SAT0437 Occurrence of Organ Involvement in Early Systemic Sclerosis. (9th June 2015) - Van Den Hombergh, W.; Fransen, J.; Knaapen-Hans, H.K.; van den Hoogen, F.H.; Vonk, M.C.
Abstract : Background: Organ involvement in systemic sclerosis (SSc) is tightly linked to survival, which is decreased in both limited cutaneous SSc (lcSSc) and diffuse cutaneous SSc (dcSSc). Early organ involvement occurs often in the first years of the disease, mainly in dcSSc (1). In the context of new emerging therapies, recognition of SSc patients prone to early organ involvement at clinical diagnosis is important. Various studies describe the occurrence of organ involvement. However, there are only a few studies in recently diagnosed SSc patients describing organ involvement at and after clinical diagnosis (2). Therefore, we want to address recent data on occurrence of organ involvement in SSc patients at the moment of diagnosis and during 5 years of follow-up. Objectives: To determine the occurrence of lung, cardiac and renal involvement at diagnosis and during 5 years of follow-up in patients with lcSSc and dcSSc Methods: The Nijmegen Systemic Sclerosis inception cohort consisted of 619 SSc patients clinically diagnosed and classified as either dcSSc or lcSSc based on skin involvement. Data on interstitial lung disease (ILD), pulmonary hypertension (PH), scleroderma renal crisis (SRC) and cardiac involvement were collected from diagnosis up to 5 years of follow-up. ILD: high-resolution CT anomalies in combination with lung function abnormalities. PH: confirmed by right heart catheterization with a mean pulmonary artery pressure of ≥25 mmHg and a pulmonary capillairy wedge pressure ≤15 mmHg. SRC: new-onset hypertension >150/85 mmHg and a decrease in eGFR of ≥30%. Cardiac involvement: ejection fraction <50% and/or left ventricular diastolic dysfunction >grade 1 and/or symptomatic pericard effusion. Kaplan Meier Curves and Log Rank tests were used for analysis. Results: The 415 patients in this study included fewer males in the lcSSc subgroup (27% vs. 47%, p<0.001), and time between the first non-Raynaud symptom and diagnosis was longer (16 vs. 8 months, p<0.001) compared to the dcSSc subgroup. Presence of ILD at diagnosis did not differ between lcSSc and dcSSc (both 19%). In lcSSc, PH was present at diagnosis in 9% compared to 4% in dcSSc (p=0.08). Presence of SRC at diagnosis was less frequent in lcSSc compared to dcSSc (0% vs. 4%, p=0.009). In 3% of lcSSc cardiac involvement at diagnosis was present compared to 4% in dcSSc (p=0.34). Median time from diagnosis to development of ILD, PH, SRC and cardiac involvement did not differ between lcSSc and dcSSc. The figures show development of organ involvement during the 5-year follow up, with differences between lcSSc and dcSSc (p<0.001 in ILD, p=0.26 in PH, p=0.004 in both SRC and cardiac involvement). Conclusions: Identification of patients at risk for early organ involvement is an important goal. Our data show occurrence of organ involvement in lcSSc and dcSSc at the moment of diagnosis and during 5-years of follow-up. This supplies us with a first key step in the development of a prediction model for early organ involvement at the moment of diagnosis. References: Steen VD, Medsger TA, Jr. Severe organ involvement in systemic sclerosis with diffuse scleroderma. Arthritis Rheum. 2000;43(11):2437-44. Epub 2000/11/18. Nihtyanova SI, Schreiber BE, Ong VH, Rosenberg D, Moinzadeh P, Coghlan JG, et al. Prediction of pulmonary complications and long-term survival in systemic sclerosis. Arthritis Rheumatol. 2014;66(6):1625-35. Epub 2014/03/05. Disclosure of Interest: None declared